Just Advisory and Maximally Representative: A Conjoint Experiment on Non-Participants' Legitimacy Perceptions of Deliberative Forums - Goldberg, Saskia (Journal of deliberative democracy, 2021)
Citizen involvement in deliberative forums is frequently discussed with an eye to boosting the legitimacy of decision-making. However, this idea has been radically challenged by Cristina Lafont (2015, 2017, 2019), who argues that deliberative forums may decrease rather than increase legitimacy. Yet Lafont’s legitimacy challenge has been primarily discussed at a theoretical level without taking the perceptions of citizens into account. Referring to an explorative student conjoint experiment this article examines how non-participants assess deliberative forums. It focuses on different authorization mechanisms and a set of institutional design features and combines them with non-participants’ substantive considerations and their awareness of such forums. Empirical findings of the student sample confirm Lafont’s critique, as they suggest that respondents want the authority of deliberative forums to be clearly circumscribed and minimal but also maximally representative and inclusive. Moreover, legitimacy perceptions are closely tied to substantive considerations and awareness of such novel and unfamiliar institutions.